2015
DOI: 10.1016/j.bbadis.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics profiling of cholangiocarcinoma exosomes: A potential role of oncogenic protein transferring in cancer progression

Abstract: Cholangiocarcinoma (CCA), a common primary malignant tumor of bile duct epithelia, is highly prevalent in Asian countries and unresponsive to chemotherapeutic drugs. Thus, a newly recognized biological entity for early diagnosis and treatment is highly needed. Exosomes are small membrane bound vesicles found in body fluids and released by most cell types including cancer cells. The vesicles contain specific subset of proteins and nucleic acids corresponding to cell types and play essential roles in pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 39 publications
2
49
0
Order By: Relevance
“…Similar results are also observed in studies with cholangiocarcinoma (CCA). A study using CCA cells derived from human patients were shown to secrete exosomes that increased migration and invasion of human cholangiocyte cell line H69 [20]. The exposure of mesenchymal stem cells to CCA cell-derived exosomes enhance their migratory capability and the release of cytokines such as CXCL1, CCL2 and IL-6 leading to cell proliferation [21].…”
Section: Cell-cell Communication Via Exosomesmentioning
confidence: 99%
“…Similar results are also observed in studies with cholangiocarcinoma (CCA). A study using CCA cells derived from human patients were shown to secrete exosomes that increased migration and invasion of human cholangiocyte cell line H69 [20]. The exposure of mesenchymal stem cells to CCA cell-derived exosomes enhance their migratory capability and the release of cytokines such as CXCL1, CCL2 and IL-6 leading to cell proliferation [21].…”
Section: Cell-cell Communication Via Exosomesmentioning
confidence: 99%
“…In particular, CCA‐derived EV were shown to stimulate secretion of the proinflammatory cytokine interleukin‐6 by mesenchymal stem cells, further promoting the growth of CCA cells . CCA‐derived EV also stimulate the invasion and migration of these cancer cells . Moreover, EV participate in the trafficking of specific microRNA species between cancer‐associated fibroblasts and CCA cells, thus regulating tumor growth .…”
Section: Discussionmentioning
confidence: 99%
“…The endocytic origin includes endosomal proteins involved in transport and fusion (annexins and flotillin), cell targeting (tetraspanins), multi-vesicular body (MVB) proteins (Alix and TSG101) [2], as well as various proteins linked to lipid metabolism [3]. Extracellular matrix and cell surface proteins such as collagens, integrins, and galectins [4], cell surface receptors and signaling molecules, intracellular cytoskeletal components, as well as metabolic enzymes and G proteins are also present [5]. In contrast to their cells of origin, exosomes are enriched in cholesterol, ceramide, phosphoglycerides, and long and saturated fatty-acyl chains, all of which may provide structural stability [2].…”
Section: Exosome Structure and Compositionmentioning
confidence: 99%